Perception of E-Budgeting Implementation: Persepsi Terhadap Implementasi E-Budgeting - Zulfiani, Alfi Eka; Biduri, Sarwenda (Indonesian Journal of Law and Economics Review, 2018)
This study aims to determine the influence of system quality, information quality and quality of human resources on the implementation of e-budgeting in Sidoarjo Regency. This study uses a quantitative method with a questionnaire as a research instrument. The sample used was 10 OPD in Sidoarjo Regency. The sampling technique in this study used purposive sampling. The data analysis technique used is validity test, reliability test and classic assumption test while the hypothesis testing in this study uses multiple linear regression analysis. The results of the research obtained based on the validity test and reliability test showed that all questions were declared valid and reliable. The results of the analysis show that the quality of the system partially influences the implementation of e-budgeting. The quality of human resources partially influences the implementation of e- budgeting. While the quality of information does not partially affect the implementation of e-budgeting.